Omitting surgery in esophageal cancer patients with complete response after neoadjuvant chemoradiotherapy: a systematic review and meta-analysis - Jaehyeon Park (BMC, 2021)
Abstract Background Neoadjuvant chemoradiotherapy (nCRT) followed by surgery is a standard treatment modality for locally-advanced esophageal cancer. However, patients who achieve clinical complete response (cCR) after nCRT have been reported to have better prognosis. Further, the role of surgery in these patients is controversial. Thus, this meta-analysis aimed to evaluate whether surgery is still useful in patients with cCR after nCRT. Methods We systematically reviewed the MEDLINE, PubMed, Embase, Cochrane library, and Scopus databases for studies on surgical efficacy in complete responders after concurrent chemoradiotherapy for esophageal cancer. The publication date was set to January 1, 2010–January 31, 2020. The hazard ratio (HR) and risk ratio were used to compare the 2-year overall survival (OS), disease-free survival (DFS), incidence of locoregional failure, distant metastasis, and treatment mortality between the nCRT and nCRT plus surgery groups. Results Six articles involving 609 patients were included. There was a significant benefit of nCRT for OS (HR = 0.80, 95% confidence interval [CI] 0.64–0.99, p = 0.04), but not for DFS (HR = 1.55, 95% CI 0.35–6.86, p = 0.56). The nCRT group tended to have lower mortality than the nCRT plus surgery group (risk ratio = 0.15, 95% CI 0.02–1.18, p = 0.07). Conclusion Omitting surgery provides better OS in complete responders after nCRT. Adding surgery could increase the morbidity and mortality and decrease the quality of life. Thus, nCRT alone could be a feasible approach for patients with cCR.